2005
DOI: 10.1002/mrc.1693
|View full text |Cite
|
Sign up to set email alerts
|

Conformational states of human H-Ras detected by high-field EPR, ENDOR, and31P NMR spectroscopy

Abstract: Ras is a central constituent of the intracellular signal transduction that switches between its inactive state with GDP bound and its active state with GTP bound. A number of different X-ray structures are available. Different magnetic resonance techniques were used to characterise the conformational states of the protein and are summarised here. 31P NMR spectroscopy was used as probe for the environment of the phosphate groups of the bound nucleotide. It shows that in liquid solution additional conformational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…This observation is in accordance with ENDOR measurements with GTP. [30] In photolysis spectra of Ras·caged-GTP (Figure 2), the bands of the equilibrated Ras·GTP state point upwards, and absorptions of the Ras· caged-GTP state point downwards. By comparing the spectra of WT and T35S Ras, we see changes in a-, b-, and g-phosphate bands; this indicates a shift to another Ras·GTP state.…”
Section: Resultsmentioning
confidence: 97%
“…This observation is in accordance with ENDOR measurements with GTP. [30] In photolysis spectra of Ras·caged-GTP (Figure 2), the bands of the equilibrated Ras·GTP state point upwards, and absorptions of the Ras· caged-GTP state point downwards. By comparing the spectra of WT and T35S Ras, we see changes in a-, b-, and g-phosphate bands; this indicates a shift to another Ras·GTP state.…”
Section: Resultsmentioning
confidence: 97%
“…The effects of metal ion binding to the 31 P chemical shifts of nucleotides have been well-documented in the literature, [12,13,20,28,29] which were used for the 31 P resonance assignments in the succeeding texts. The characteristic 31 P signal for GTP is the resonance of betaphosphate (P β ).…”
Section: The Gtp In Microtubulesmentioning
confidence: 99%
“…[19] 31 P NMR spectroscopy has been successfully used for detecting the conformations of GTP-binding enzymes in solution [20,21] or in crystals. [12,13] In previous work, we have successfully reported a 31 P cross-polarization magic angle spinning (CPMAS) NMR spectrum obtained from lyophilized microtubules, [22] where the signal-to-noise ratio (SNR = 7.5) was not sufficient enough to provide quantitative information. Here, we report a 31 P CPMAS NMR spectrum of lyophilized, paclitaxel-stabilized microtubules with enhanced resolution (SNR = 25) and show that it is now possible to study the molecular environments in detail for the guanine nucleotides in microtubules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, we have demonstrated that highfield EPR in liquid solution revealed important differences in the number of water ligands between the wild-type and the G12V oncogenic mutant of the protein in both switch states. 27,28 We have recently employed pulsed ENDOR spectroscopy at 94 GHz to investigate these differences in more detail. 29 Here, we present the first representative application of 180-GHz pulsed 1 H-ENDOR in the study of Ras ž Mn 2C ž GDP.…”
Section: Endor On Ras ž Mn 2+ ž Gdpmentioning
confidence: 99%